Fatty Acid Mixtures from Nigella sativa Protects PC12 Cells from Oxidative Stress and Apoptosis Induced by Doxorubicin - Leila Hosseinzadeh; Shima Soheili; Nastaran Ghiasvand; Farahnaz Ahmadi; Yalda shokoohinia (Tabriz University of Medical Sciences, 2018)
Background: Fatty acids (FAs), the key structural elements of dietary lipids, are notable in the nutritional value of plants. Black cumin, a popular anti-inflammatory and antioxidant food seasoning, contains nonpolar constituents such as FAs. Methods: Seeds were extracted using hexane and their cytoprotective activity was assessed against doxorubicin (DOX)-mediated oxidative stress and apoptosis in PC12 cell line. Results: In spite of the cellular death induced by DOX toward PC12 cells, bioassay-guided purification showed that pretreatment with FAs mixtures (24h) attenuated DOX-mediated apoptosis, which could be attributed to the inhibited caspase 3 activity and enhanced mitochondrial membrane potential. Palmitic acid, caprylic acid and oleic acid each 1/3 in the mixture, also suppressed DOX-induced ROS generation. Conclusion: Our observation indicated that the subtoxic concentration of FAs from Nigella sativa could effectively protect the cells against oxidative stress, due to their antioxidant activity, and could be regarded as a dietary supplement.